Low dielectric material and applications thereof
Patent Information
- Application Number
- CN202611144501.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-23
AI Technical Summary
然而,这类高性能单体的合成路线通常较为复杂,原料成本高,且其预聚物的粘度调控、固化交联密度与加工流变性之间往往存在矛盾
1. 本申请通过各组分复配得到的低介电材料,其经固化后形成由联苯、茚环刚性骨架及多官能度乙烯基构成的高交联密度三维网络。该交联网络赋予低介电材料的固化产物极低的介电损耗、优异的玻璃化转变温度以及较低的热膨胀系数,能够有效满足高频高速信号传输的严苛需求。同时,低介电材料具有原料成本低廉、制备条件温和的优势。
Smart Images

Figure CN122958797A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of low-dielectric materials technology, and in particular to a low-dielectric material and its applications. Background Technology
[0002] With the rapid development of fifth-generation (5G) and higher frequency communication technologies, electronic devices are increasingly demanding higher signal transmission rates and bandwidths. Printed circuit board and semiconductor packaging materials must possess lower dielectric constants and dielectric losses to effectively reduce insertion loss and delay during signal transmission. Currently, conventional hydrocarbon resins, such as polybutadiene resin, polyphenylene ether resin, and styrene-butadiene copolymer, while possessing certain low dielectric properties, still have significant shortcomings in dielectric loss, heat resistance, and coefficient of thermal expansion, making it difficult to meet the stringent requirements for comprehensive material performance in high-frequency, high-speed, and high-reliability applications.
[0003] In existing technologies, to improve the dielectric and heat resistance properties of hydrocarbon resins, researchers have attempted to introduce large-volume skeletons such as rigid aromatic rings, biphenyl rings, or naphthalene rings into the molecular structure to suppress molecular chain segment polarization and improve thermal stability. However, the synthetic routes for these high-performance monomers are usually complex, with high raw material costs, and there are often contradictions between the viscosity control of their prepolymers, the curing crosslinking density, and the processing rheology. Furthermore, in the actual preparation of low-dielectric materials, if only high-rigidity monomers are relied upon, the cured products are often brittle and have insufficient interlayer bonding. At the same time, severe glue residue is prone to occur during high-temperature pressing due to the excessively low viscosity of the system, affecting the thickness uniformity and yield of the boards.
[0004] Therefore, there is an urgent need to provide a low-dielectric material that combines excellent dielectric properties, high heat resistance, good processing reliability, and low cost. Summary of the Invention
[0005] The purpose of this invention is to provide a low-dielectric material and its application, which combines excellent dielectric properties, high heat resistance, good processing reliability, and low cost.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a low dielectric material, the low dielectric material comprising the following raw materials in parts by weight: 5-80 parts of indene-containing monomers and / or indene-containing resins, 5-40 parts of unsaturated polydiene resins, 5-40 parts of saturated hydrocarbon resins, 30-120 parts of fillers, 0.3-10 parts of thermal initiators, 10-50 parts of flame retardants, and 0-30 parts of crosslinking agents.
[0007] Optionally, the low-dielectric material further includes 30-65 parts by weight of reinforcing material.
[0008] Optionally, the molar content of unsaturated carbon-carbon double bonds in the unsaturated polydiene resin is 2%-20%.
[0009] Optionally, the unsaturated polydiolefin resin has a viscosity of 0.1-100 Pa·s at 25°C, or the unsaturated polydiolefin resin is solid at 25°C.
[0010] Optionally, the number-average molecular weight of the unsaturated polydiolefin resin is 1000-10000.
[0011] Optionally, the saturated hydrocarbon resin has a number average molecular weight of 1,000-100,000, and includes one or more of saturated polybutadiene resin, hydrogenated styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer.
[0012] Optionally, the low-dielectric material further includes 30-65 parts by weight of reinforcing material.
[0013] Optionally, the structural formula of the indene-containing monomer is: (1), R1 is independently selected from any one of hydrogen atom, methyl, methoxy, ethyl, and ester group; R2 is selected from any one of hydrogen atom, methyl, methoxy, ethyl, or ester group; R3 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, or aliphatic chains containing 1-10 carbon atoms; R4 is selected from any one of hydrogen atom, methoxy group, ester group, or aliphatic chain containing 1-10 carbon atoms; R5 is selected from any one of hydrogen atoms, methoxy groups, or aliphatic chains containing 1 to 10 carbon atoms; R6 is selected from any one of the following: phenyl, naphthyl, biphenyl, aromatic alkyl, aliphatic chain containing 1-10 carbon atoms, or a substituent containing halogen atoms.
[0014] Optionally, the method for preparing the indene-containing monomer includes the following steps: A1. Under an inert atmosphere, a compound containing two chloromethyl groups and indene are dissolved in toluene, and tetrabutylammonium bromide and phenothiazine are added. A first alkali solution is added, and the reaction is carried out at 25℃-80℃ for 1-20 hours. After the reaction is completed, the reaction solution is obtained. A2. Add an aromatic compound containing monochloromethyl to the reaction solution obtained in step A1, add a second alkali solution, and react at 25℃-80℃ for 1-20h to obtain an indene-containing monomer with the structural formula shown in formula (1).
[0015] Optionally, in step A1, the molar ratio of the compound containing two chloromethyl groups to indene is (0.45-0.55):1, the molar ratio of tetrabutylammonium bromide to indene is (0.01-0.1):1, the molar ratio of phenothiazine to indene is (0.001-0.01):1, and the molar ratio of alkali to indene in the first alkaline solution is (3-4.5):1. In step A2, the molar ratio of the aromatic compound containing monochloromethyl to indene is (0.9-1.3):1, and the molar ratio of the alkali to indene in the second alkaline solution is (3-4.5):1. The alkali in the first alkaline solution and the second alkaline solution is selected from one or two of lithium hydroxide, potassium hydroxide, and sodium hydroxide.
[0016] Optionally, the structural formula of the indene-containing resin is: (2) or (3), In structural formulas (2) and (3), CO represents the polymerization of monomer (1) and monomer M2: R1 is independently selected from any one of hydrogen atom, methyl, methoxy, ethyl, and ester group; R2 is selected from any one of hydrogen atom, methyl, methoxy, ethyl, or ester group; R3 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, or aliphatic chains containing 1-10 carbon atoms; R4 is selected from any one of hydrogen atom, methoxy group, ester group, or aliphatic chain containing 1-10 carbon atoms; R5 is selected from any one of hydrogen atoms, methoxy groups, or aliphatic chains containing 1 to 10 carbon atoms; R6 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, aliphatic chain containing 1-10 carbon atoms, or a substituent containing halogen atoms; n is selected from integers ≥1 and ≤1000; m is selected from integers ≥ 0 and ≤ 1000; m' is selected from integers ≥0 and ≤1000; And m+n+m'≥2; When the indene-containing resin is polymerized, R7 is an independent terminal or hydrogen atom of the initiator; When the indene-containing resin is not polymerized, R7 is independent of each other. Or hydrogen atoms.
[0017] Optionally, in structural formulas (2) and (3), M2 is selected from at least one of styrene, methylstyrene, bistyrene, naphthalene, divinylbenzene, divinylbiphenyl, methacrylate, acrylate, maleimide, maleic anhydride, butadiene, isoprene, ethylene, propylene, norbornene, and ethylidene norbornene.
[0018] Optionally, n is selected from integers ≥2 and ≤200, and m is selected from integers ≥0 and ≤100.
[0019] Optionally, the initiator is terminated in a naphthalene ring, n-butyl, tert-butyl, benzoyloxy, phenyl, isopropylphenoxy, or tert-butoxy.
[0020] Optionally, the preparation method of indene-containing resin includes the following steps: polymerizing or copolymerizing indene-containing monomers with other monomers to form a prepolymer, thereby obtaining indene-containing resin.
[0021] Optionally, the polymerization is thermally initiated polymerization or free radical polymerization; the reaction temperature of the thermally initiated polymerization is 40℃-100℃, and the reaction time is 1-20h; the reaction temperature of the free radical polymerization is 40℃-100℃, and the reaction time is 1-20h.
[0022] Optionally, the other monomers are selected from at least one monomer selected from styrene, methylstyrene, bistyrene, naphthalene, divinylbenzene, divinylbiphenyl, methacrylates, acrylates, maleic anhydride, maleimide, butadiene, isoprene, ethylene, propylene, norbornene, and ethylene-imide norbornene.
[0023] A second aspect of the present invention provides a prepreg made of a low-dielectric material containing reinforcing material.
[0024] A third aspect of the present invention provides a semiconductor device comprising a cured product of the low-dielectric material described in the first aspect, or a sheet-like cured product comprising the prepreg described in the second aspect.
[0025] Compared with the prior art, the technical solution of the present invention has the following technical effects: 1. The low-dielectric material obtained by compounding the components in this application forms a highly cross-linked three-dimensional network after curing, consisting of a rigid biphenyl and indene ring framework and multifunctional vinyl groups. This cross-linked network endows the cured product of the low-dielectric material with extremely low dielectric loss, excellent glass transition temperature, and low coefficient of thermal expansion, effectively meeting the stringent requirements of high-frequency and high-speed signal transmission. Simultaneously, the low-dielectric material has the advantages of low raw material cost and mild preparation conditions.
[0026] 2. In low-dielectric materials, unsaturated polydiolefin resins can undergo prepolymerization reactions with indene-containing monomers at lower temperatures, inhibiting the high-temperature volatilization of indene-containing monomers and increasing the system viscosity and crosslinking density, thereby improving the problem of adhesive residue during hot pressing. Meanwhile, saturated hydrocarbon resins, with their higher bulk viscosity and excellent flexibility, further reduce the risk of adhesive residue while compensating for the brittleness of indene-containing resin cured products, simultaneously improving the toughness, impact resistance, and interlayer bonding of the cured products. Furthermore, the introduction of flame retardants effectively improves the flame retardant safety of low-dielectric materials and exhibits good compatibility with resin components, ensuring the safety and reliability of end applications while maintaining the low dielectric loss and high heat resistance of the cured products. Attached Figure Description
[0027] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the indene-containing monomer prepared according to Example 1 of the present invention; Figure 2 The image shows the carbon NMR spectrum of the indene-containing monomer prepared according to Example 1 of the present invention. Detailed Implementation
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0030] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of the invention. Various modifications and variations to the specific embodiments described in this specification are apparent to those skilled in the art without departing from the scope or spirit of the invention. Other embodiments derived from this specification will be apparent to those skilled in the art. This application specification and embodiments are merely exemplary.
[0031] In this application, the low-dielectric material comprises the following raw materials in parts by weight: 5-80 parts of indene-containing monomers and / or indene-containing resins, 5-40 parts of unsaturated polydiolefin resins, 5-40 parts of saturated hydrocarbon resins, 30-120 parts of fillers, 0.3-10 parts of thermal initiators, 10-50 parts of flame retardants, and 0-30 parts of crosslinking agents.
[0032] By introducing indene vinyl monomers and / or resins, the cured products of low-dielectric materials possess both extremely low dielectric loss and good heat resistance, meeting the application requirements of high-frequency signal transmission (e.g., transmission rates ≥ 56G). Unsaturated polydiolefin resins can undergo prepolymerization reactions with indene vinyl monomers at lower temperatures. This effectively suppresses the volatilization loss of indene vinyl monomers, improves raw material utilization, and increases crosslinking density. Furthermore, it increases overall viscosity, thereby improving the problem of glue residue during hot pressing, reducing equipment contamination risks, and ensuring uniform sheet thickness. Simultaneously, the additional saturated hydrocarbon resin introduced into the system plays a further synergistic role. Its high bulk viscosity (e.g., > 10000 mPa·s) helps further suppress glue residue, and the saturated hydrocarbon resin itself has good flexibility, effectively improving the brittleness defect of the rigid cured products of indene vinyl resins.
[0033] Fillers can improve the strength of low-dielectric materials and impart good thermal conductivity. Fillers can be one or more of the following: silica, alumina, titanium dioxide, zinc oxide, zirconium oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, silicon aluminum carbide, silicon carbide, mica, boehmite, calcined talc, talc, silicon nitride, calcined kaolin, potassium titanate fiber, silicon carbide single crystal fiber, silicon nitride fiber, alumina single crystal fiber, chopped glass fiber, chopped carbon fiber, chopped graphite fiber, polytetrafluoroethylene powder, polyphenylene sulfide powder, and polystyrene powder. In this application, the term "multiple" refers to two or more types. Further, the surface of the aforementioned inorganic fillers such as silica can be modified with a coupling agent. Preferably, the filler weight percentage is 50-80 parts.
[0034] Thermal initiators can initiate cross-linking polymerization reactions of unsaturated raw materials such as indene-containing monomers / resins and unsaturated polydiene resins in low-dielectric materials at a certain temperature, thereby improving the strength of the cured low-dielectric materials and enhancing the compatibility between the resin materials and fillers. Thermal initiators can be one or more of the following, including but not limited to ammonium persulfate, potassium persulfate, hydrogen peroxide, benzoyl peroxide, tert-butyl peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl hydroperoxide, diisopropyl percarbonate, and cyclohexane peroxide. Preferably, the weight percentage of the thermal initiator is 0-5 parts.
[0035] Flame retardants can include one or more of halogenated, phosphorus-based, and nitrogen-based flame retardants. Halogenated flame retardants are generally bromine-based flame retardants, such as decabromodiphenyl ethane, decabromodiphenyl ether, bromotriazine, tetrabromophenyl o-dicarboximide, tetrabromobisphenol A, brominated polystyrene, brominated epoxy resin, etc. Phosphorus-based flame retardants can be one or more of phosphazene flame retardants (e.g., hexaphenoxycyclophosphinitrogen or SPB-100, SPV-100, BP-PZ, etc. purchased from Otsuka Chemicals, Japan), phosphate ester flame retardants (PX-200 purchased from Daihachi Chemicals, Japan), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, melamine polyphosphate, etc.
[0036] Unsaturated polydiene resins can specifically include polybutadiene resin, styrene-butadiene resin (i.e., butadiene-styrene copolymer resin), polycyclopentadiene resin, polyisoprene resin, styrene-isoprene block copolymer resin, and polydiene-based benzene resin.
[0037] Preferably, the indene-containing monomer and / or indene-containing resin comprises 25-40 parts by weight, and the weight percentages of the indene-containing monomer and / or indene-containing resin can be 25, 27, 30, 34, 36, 38, or 40 parts. In some embodiments, the weight percentages of the indene-containing monomer and / or indene-containing resin comprises 25-35 parts.
[0038] Preferably, the low-dielectric material includes indene-containing monomers and indene-containing resins. Since the low-dielectric material contains both indene-containing monomers and indene-containing resins, its cured product can better achieve lower dielectric loss.
[0039] Preferably, the unsaturated polydiolefin resin is present in 5-20 parts by weight.
[0040] Preferably, the saturated hydrocarbon resin is in the form of 5-20 parts by weight.
[0041] In this application, the molar content of unsaturated carbon-carbon double bonds in the unsaturated polydiolefin resin is 2%-20%.
[0042] Unsaturated polydiolefin resins contain unsaturated carbon-carbon double bonds in their molecular structure, typically two or more. The molar content of unsaturated carbon-carbon double bonds is the ratio of the number of moles of double bonds in the resin to the total number of moles of repeating units. The molar content of unsaturated carbon-carbon double bonds in unsaturated polydiolefin resins ranges from 2% to 20%, for example, 2%, 8%, 15%, 18%, or 20%. The lower limit (≥2%) ensures that the unsaturated polydiolefin resin has a sufficient amount of active double bonds to fully prepolymerize with indene-containing monomers, thereby effectively suppressing the high-temperature volatilization of indene-containing monomers and improving the system viscosity, optimizing the residue phenomenon during hot pressing. The upper limit (≤20%) limits the number of residual unsaturated bonds in the three-dimensional network after curing, avoiding increased dielectric loss due to the polarization effect of excessive unreacted double bonds. Based on this content setting, low-dielectric materials can maintain good processing adaptability while also ensuring excellent low dielectric loss characteristics of the final cured product.
[0043] In this application, the viscosity of the unsaturated polydiolefin resin at 25°C is 0.1-100 Pa·s, or the unsaturated polydiolefin resin is solid at 25°C.
[0044] Unsaturated polydiolefin resins that are solid or liquid with suitable viscosity at room temperature are beneficial for reducing the volatilization of indene-containing monomers, ensuring suitable viscosity in low-dielectric materials, minimizing raw material loss, and guaranteeing good workability. The viscosity of unsaturated polydiolefin resins at 25°C can be, for example, 0.1 Pa·s, 10 Pa·s, 30 Pa·s, 50 Pa·s, 80 Pa·s, or 100 Pa·s.
[0045] In this application, the number average molecular weight of the unsaturated polydiolefin resin is 1000-10000.
[0046] By limiting the number-average molecular weight of unsaturated polydiolefin resins, it is possible to ensure that low-dielectric materials maintain excellent processing rheological properties during coating, impregnation, and hot-pressing processes, and to provide a uniform, stable, and appropriately cross-linked three-dimensional network structure for the final cured product. The number-average molecular weight of the unsaturated polydiolefin resins can be, for example, 1000, 2500, 4000, 7000, 9000, or 10000.
[0047] Preferably, the number average molecular weight of the unsaturated polydiolefin resin is 2000-10000.
[0048] In this application, the number average molecular weight of the saturated hydrocarbon resin is 1,000-100,000, and it includes one or more of the following: saturated polybutadiene resin, hydrogenated styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer.
[0049] Saturated hydrocarbon resins have a relatively high number-average molecular weight and high viscosity, which is beneficial for increasing the viscosity of low-dielectric material systems and reducing residue. Preferably, the number-average molecular weight of saturated hydrocarbon resins is 1000-80000.
[0050] This application also provides a prepreg made from a low-dielectric material containing reinforcing material.
[0051] For example, it can be obtained by baking low-dielectric materials containing reinforcing materials and solvents.
[0052] Specifically, the preparation method of the prepreg includes the following steps: S1. Mix indene monomers and / or indene resins, unsaturated polydiolefin resins, saturated hydrocarbon resins, fillers, thermal initiators, flame retardants and crosslinking agents with solvents to obtain a glue solution; S2. The reinforcing material is impregnated in the adhesive solution obtained in step S1 to obtain a low dielectric material, which is then baked to obtain a semi-cured sheet.
[0053] In step S1, the adhesive, due to its high reactivity, not only achieves a high glass transition temperature and excellent mechanical strength in its cured substrate, but also resists adhesion during the preparation of the prepreg. Therefore, there is no need to add a large amount of filler to improve the anti-sticking performance, effectively avoiding the adverse effects of increased processing difficulty and decreased peel strength caused by excessive filler. The solvent content in the adhesive can be 25wt%-40wt%, and the solvent can be one or more of butanone, propylene glycol monomethyl ether, toluene, xylene, etc. Furthermore, the system composed of the indene-containing monomer and / or indene-containing resin, unsaturated polydiolefin resin, saturated hydrocarbon resin, filler, thermal initiator, flame retardant, and optional crosslinking agent can be referred to as a "resin composition." The content of the resin composition in the above adhesive can be 60wt%-75wt%.
[0054] In step S1, the reinforcing material is mainly a continuous fiber cloth, wherein the continuous fiber can be one or more of the following: glass fiber (such as Q glass fiber, D glass fiber, S glass fiber, T glass fiber, E glass fiber, etc.), carbon fiber, quartz fiber, aramid fiber, polyester fiber, polyethylene (PE) fiber, polytetrafluoroethylene (PTFE) fiber, polyphenylene sulfide fiber, LCP (liquid crystal polymer) fiber, etc.
[0055] In step S2, the reinforcing material (prepreg) impregnated with the above-mentioned adhesive is baked at a temperature of 80°C-160°C for 1 min-20 min, which can transform it into a semi-cured state and evaporate and remove some of the solvent.
[0056] This application also provides a semiconductor device comprising a cured product of the aforementioned low-dielectric material, or a sheet-like cured product comprising the aforementioned prepreg.
[0057] As mentioned above, the cured product of the low-dielectric material of this application can be used as an interlayer dielectric layer material, disposed between adjacent chips in semiconductor devices. Typically, this type of interlayer dielectric layer material does not contain reinforcing materials. Furthermore, the cured product without reinforcing materials can also be used as an underfill adhesive, encapsulation material, or photoresist layer material in semiconductor devices. Additionally, the cured product of the low-dielectric material and the sheet-like cured product of the aforementioned prepreg can also be used as an insulating resin material in the field of printed circuit boards.
[0058] In all the preparation examples, embodiments, and comparative examples below, the raw materials and reagents used were commercially available. The unsaturated polydiolefin resin was selected from polybutadiene resin (purchased from Nippon Soda Co., Ltd.), with a number-average molecular weight of 3000, a viscosity of 2.1 Pa·s at 25°C, and a molar content of 12% unsaturated carbon-carbon double bonds. The saturated hydrocarbon resin was selected from hydrogenated polybutadiene (purchased from Nippon Soda Co., Ltd., BI-3000), with a number-average molecular weight of 3000.
[0059] Preparation Example 1 A method for preparing indene-containing monomers includes the following steps: A1. Under nitrogen protection, 4,4'-dichloromethylbiphenyl (12.56 g, 0.05 mol) and indene (11.62 g, 0.1 mol) were dissolved in 80 mL of toluene, and tetrabutylammonium bromide (1.61 g, 0.005 mol) and phenothiazine (0.1 g, 0.0005 mol) were added. After stirring until the solids dissolved, a first alkaline solution prepared by dissolving sodium hydroxide solid (16 g, 0.4 mol) in an appropriate amount of deionized water (about 30 mL) was slowly added dropwise. After the addition was completed, the reaction was carried out at 60 °C for 8 h to obtain the reaction solution. A2. Add 15.26 g (0.1 mol) of 4-vinylbenzyl chloride to the reaction solution obtained in step A1, and then slowly add a second alkaline solution prepared by dissolving 16 g (0.4 mol) of sodium hydroxide solid in an appropriate amount of deionized water (about 30 mL). After the addition is complete, react at 70 °C for 9 h. After the reaction is completed, lower the temperature to 25 °C, add deionized water to remove excess sodium hydroxide, and then add sodium bisulfate to adjust the pH to 4.5. Then wash the organic phase with deionized water (shake and let it stand to separate the layers, remove the aqueous layer) until neutral (pH≈7). Finally, remove the toluene solvent by vacuum distillation of the organic phase to obtain an indene-containing monomer with the structural formula shown in formula (1-A): (1-A).
[0060] Depend on Figure 1 It can be seen that the multiple resonance peaks in the chemical shift range of 6.5-7.8 ppm are attributed to aromatic protons on the biphenyl skeleton, indene ring, and vinyl benzyl group, as well as olefin protons on the indene ring. The characteristic multiple peaks appearing in the 5.2-6.5 ppm region correspond to olefin protons of the terminal vinyl group (-CH=CH2), and the multiple peaks in the 3.6-4.2 ppm range correspond to the methylene (-CH2-) protons connecting biphenyl to the indene ring, and between the indene ring and the vinyl benzyl group. Figure 2 It can be seen that the dense absorption peaks in the 120-150 ppm range are attributed to the aromatic ring and unsaturated olefin carbon atoms, while multiple signals in the 30-50 ppm range correspond to the methylene carbon atoms in the molecule. All characteristic signals and peak shapes of the proton and carbon NMR spectra are consistent with the structure of the indene-containing monomer of formula (1-A), and the symmetrical distribution characteristics of the spectral signals are consistent with the centrosymmetric skeleton structure of the indene-containing monomer, confirming that the indene-containing monomer obtained in Example 1 is the target compound.
[0061] Preparation Example 2 A method for preparing indene-containing monomers includes the following steps: A1. Under nitrogen protection, 3,3'-dichloromethylbiphenyl (27.63 g, 0.11 mol) and indene (23.24 g, 0.2 mol) were dissolved in 150 mL of toluene, and tetrabutylammonium bromide (5.16 g, 0.016 mol) and phenothiazine (0.28 g, 0.0014 mol) were added. After stirring until the solids dissolved, a first alkaline solution prepared by dissolving sodium hydroxide solid (36 g, 0.9 mol) in an appropriate amount of deionized water (about 60 mL) was slowly added dropwise. After the addition was completed, the reaction was carried out at 55 °C for 12 h. During this period, the reaction degree was monitored by thin-layer chromatography (TLC) until the raw material indene was basically reacted, and the reaction solution was obtained. A2. 1-(chloromethyl)-4-vinylnaphthalene (48.64 g, 0.24 mol) was added to the reaction solution obtained in step A1. Then, a second alkaline solution prepared by dissolving 28 g, 0.7 mol of solid sodium hydroxide in an appropriate amount of deionized water (approximately 45 mL) was slowly added dropwise. After the addition was complete, the reaction was carried out at 80 °C for 8 h, during which the reaction degree was monitored by thin-layer chromatography (TLC) until the reaction was complete. After the reaction was completed, the temperature was lowered to 25 °C. Deionized water was added first to remove excess sodium hydroxide, and then sodium bisulfate was added to adjust the pH to 4. The organic phase was then washed with deionized water until neutral (pH≈7). Finally, the organic phase was subjected to vacuum distillation to remove the toluene solvent, yielding an indene-containing monomer with the structural formula shown in formula (1-B). (1-B).
[0062] Preparation Example 3 A method for preparing indene-containing resins includes the following steps: B1. Under nitrogen protection, add 13.2 g (approximately 0.025 mol) of indene-containing monomer (1-A) as shown in Preparation Example 1, and seal with a rubber stopper. B2. Under nitrogen protection, 20 mL of toluene was added, and a thermally initiated polymerization reaction was carried out at 100 °C for 10 h. After the reaction was completed, the mixture was cooled to room temperature, and then the reaction solution was slowly added dropwise to a large amount of methanol for precipitation. The precipitate was collected by filtration, and the resulting solid product was washed repeatedly with methanol three times and dried to obtain an indene-containing resin with the structural formula shown in formula (2). (2), Where m=0, CO represents the indene-containing monomer unit of formula (1-A) in Preparation Example 1, R1, R2, R4, and R5 are all hydrogen atoms, R3 is phenyl, R6 is biphenyl, and one of the two R7s is... The other is a hydrogen atom.
[0063] Preparation Example 4 A method for preparing indene-containing resins includes the following steps: B1. Under nitrogen protection, add the indene-containing monomer (13.2 g, about 0.025 mol) and styrene (5.2 g, about 0.05 mol) of formula (1-A) obtained in Preparation Example 1, and stopper the flask with a rubber stopper. B2. Under nitrogen protection, 25 mL of toluene was added, and a thermally initiated polymerization reaction was carried out at 100 °C for 11 h. After the reaction was completed, the mixture was cooled to room temperature, and then the reaction solution was slowly added dropwise to a large amount of methanol for precipitation. The precipitate was collected by filtration, and the resulting solid product was washed repeatedly with methanol three times and dried to obtain an indene-containing resin with the structural formula shown in formula (2). (2), Where m is the degree of polymerization of the styrene segment unit, CO represents the copolymerization linkage point between the indene-containing monomer unit and the styrene unit in preparation example (1-A), R1, R2, R4, and R5 are all hydrogen atoms, R3 is phenyl, R6 is biphenyl, M2 is styrene, and one of the two R7s is... The other is a hydrogen atom.
[0064] Preparation Example 5 A method for preparing indene-containing resins includes the following steps: B1. Under nitrogen protection, add the indene-containing monomer (13.2 g, about 0.025 mol) and styrene (10.4 g, about 0.1 mol) of formula (1-A) obtained in Preparation Example 1, and stopper the flask with a rubber stopper. B2. Under nitrogen protection, 25 mL of toluene was added, and the thermally initiated polymerization reaction was carried out at 85 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and then the reaction solution was slowly added dropwise to a large amount of methanol for precipitation. The precipitate was collected by filtration, and the obtained solid product was washed repeatedly with methanol 3 times and dried to obtain an indene-containing resin with the structural formula shown in formula (3): (3), Where m and m' represent the average degree of polymerization of the styrene segment, R1, R2, R4, and R5 are all hydrogen atoms, R3 is phenyl, R6 is biphenyl, M2 is styrene, and one of the two R7s is... The other is a hydrogen atom.
[0065] The technical solution of the present invention will be further explained and illustrated below through specific embodiments.
[0066] Preparation Example 6 Preparation Example 6 provides a method for preparing an indene-containing monomer, which differs from Preparation Example 1 in that the mass of 3,3'-dichloromethylbiphenyl is adjusted to 20.1 g.
[0067] Preparation Example 7 Preparation Example 7 provides a method for preparing an indene-containing monomer, which differs from Preparation Example 1 in that the mass of 4-vinylbenzyl chloride is adjusted to 31 g.
[0068] Preparation Example 8 Preparation Example 8 provides a method for preparing an indene-containing monomer, which differs from Preparation Example 1 in that sodium hydroxide in steps A1 and A2 is replaced with an equimolar amount of sodium carbonate.
[0069] Preparation Example 9 Preparation of benzocyclobutene monosubstituted divinyl monomer: After evacuating the C1 5L reactor and purging with nitrogen three times, 4-bromobenzocyclobutene (2.5 mol), divinylbenzene (7.5 mol), palladium acetate (0.0075 mol), tris(o-methylphenyl)phosphine (0.03 mol), triethylamine (2.63 mol), and dry acetonitrile (2 L) were added. The system was then purged with nitrogen once more and heated to 58°C in a water bath. The reaction was stopped after 48 hours. The reaction extent was monitored by TLC during the process. A large amount of salt precipitated after the system returned to room temperature. C2. Remove solids and palladium black by vacuum filtration. Concentrate the filtrate by rotary evaporation to remove the solvent, and then filter it with silica gel. Remove unreacted raw materials by vacuum distillation of the filtrate obtained in this filtration at 85°C using an oil pump to obtain a brownish-yellow liquid (which solidifies after cooling). C3. Then, the raw material is further removed by vacuum distillation using an oil pump at 90°C using a short-path distillation apparatus. C4. Finally, a short-path distillation apparatus was used again at 150°C to obtain a high-purity benzocyclobutene monosubstituted divinylbenzene monomer by vacuum distillation with an oil pump.
[0070] Example 1 The low dielectric material comprises the following raw materials in parts by weight: 25 parts of indene-containing monomer (prepared from Preparation Example 1), 15 parts of indene-containing resin (prepared from Preparation Example 3), 10 parts of polybutadiene resin, 5 parts of hydrogenated polybutadiene, 0.5 parts of benzoyl peroxide, 50 parts of spherical silica, 15 parts of decabromodiphenyl ethane, and 2 parts of triallyl isocyanurate.
[0071] The method for preparing a prepreg includes the following steps: S1. Dissolve indene-containing monomers, indene-containing resins, polybutadiene resins, hydrogenated polybutadiene, spherical silica, benzoyl peroxide, decabromodiphenyl ethane, and triallyl isocyanurate in a mixed solvent of methyl ethyl ketone (MEK) and toluene in a volume ratio of 1:1 to obtain a glue solution; the MEK and toluene content in the glue solution is 30 wt%, and the resin composition content is 70 wt%. S2. Impregnate E glass fiber cloth in the adhesive solution obtained in step S1 to obtain a low dielectric material, and bake it at 140°C for 4 minutes to obtain a semi-cured sheet.
[0072] Preparation of the laminate: Stack two prepreg sheets as described above, attach copper foil to their opposite sides, place them in a press, and hot press for 1 hour at a temperature of 210℃ and a pressure of 2.0MPa to obtain the laminate.
[0073] Example 2 The low dielectric material comprises the following raw materials in parts by weight: 20 parts of indene-containing monomer (prepared from Preparation Example 2), 20 parts of indene-containing resin (prepared from Preparation Example 4), 20 parts of polybutadiene resin, 20 parts of hydrogenated polybutadiene, 5 parts of benzoyl peroxide, 75 parts of spherical silica, 30 parts of decabromodiphenyl ethane, and 15 parts of triallyl isocyanurate.
[0074] The method for preparing a prepreg includes the following steps: S1, indene-containing monomers, indene-containing resins, polybutadiene resins, hydrogenated polybutadiene, spherical silica, benzoyl peroxide, decabromodiphenyl ethane, and triallyl isocyanurate are dissolved in a mixed solvent of butanone and toluene in a volume ratio of 1:1 to obtain a glue solution; the content of butanone and toluene in the glue solution is 35 wt%, and the content of the resin composition is 65 wt%. S2. Impregnate E glass fiber cloth in the adhesive solution obtained in step S1 to obtain a low dielectric material, and bake it at 150°C for 3 minutes to obtain a semi-cured sheet.
[0075] The preparation of the laminate is the same as in Example 1.
[0076] Example 3 The low dielectric material comprises the following raw materials in parts by weight: 5 parts of indene-containing monomer (prepared from Preparation Example 1), 5 parts of indene-containing resin (prepared from Preparation Example 3), 5 parts of polybutadiene resin, 30 parts of hydrogenated polybutadiene, 0.3 parts of benzoyl peroxide, 30 parts of spherical silica, 15 parts of decabromodiphenyl ethane, and 2 parts of triallyl isocyanurate.
[0077] The method for preparing a prepreg includes the following steps: S1. Dissolve indene-containing monomers, indene-containing resins, polybutadiene resins, hydrogenated polybutadiene, spherical silica, benzoyl peroxide, decabromodiphenyl ethane, and triallyl isocyanurate in a mixed solvent of methyl ethyl ketone (MEK) and toluene in a volume ratio of 1:1 to obtain a glue solution; the MEK and toluene content in the glue solution is 25 wt%, and the resin composition content is 75 wt%. S2. Impregnate E glass fiber cloth in the adhesive solution obtained in step S1 to obtain a low dielectric material, and bake it at 120°C for 8 minutes to obtain a semi-cured sheet.
[0078] The preparation of the laminate is the same as in Example 1.
[0079] Example 4 The low dielectric material comprises the following raw materials in parts by weight: 50 parts of indene-containing monomer (prepared from Preparation Example 2), 30 parts of indene-containing resin (prepared from Preparation Example 5), 40 parts of polybutadiene resin, 40 parts of hydrogenated polybutadiene, 10 parts of benzoyl peroxide, 120 parts of spherical silica, 50 parts of decabromodiphenyl ethane, and 30 parts of triallyl isocyanurate.
[0080] The method for preparing a prepreg includes the following steps: S1, indene-containing monomers, indene-containing resins, polybutadiene resins, hydrogenated polybutadiene, spherical silica, benzoyl peroxide, decabromodiphenyl ethane, and triallyl isocyanurate are dissolved in a mixed solvent of butanone and toluene in a volume ratio of 1:1 to obtain a glue solution; the content of butanone and toluene in the glue solution is 40 wt%, and the content of the resin composition is 60 wt%. S2. Impregnate E glass fiber cloth in the adhesive solution obtained in step S1 to obtain a low dielectric material, and bake it at 150°C for 3 minutes to obtain a semi-cured sheet.
[0081] The preparation of the laminate is the same as in Example 1.
[0082] Comparative Example 1 Comparative Example 1 provides a method for preparing a low-dielectric material and a prepreg, which differs from Example 2 in that the indene-containing monomer is obtained from Preparation Example 6.
[0083] Comparative Example 2 Comparative Example 2 provides a method for preparing a low dielectric material and a prepreg, which differs from Example 2 in that the indene-containing monomer is obtained from Preparation Example 7.
[0084] Comparative Example 3 Comparative Example 3 provides a method for preparing a low dielectric material and a prepreg, which differs from Example 2 in that the indene-containing monomer is obtained from Preparation Example 8.
[0085] Comparative Example 4 Comparative Example 4 provides a method for preparing a low dielectric material and a prepreg. The difference from Example 2 is that the indene-containing monomer is replaced with an equal amount of benzocyclobutene monosubstituted divinylbenzene monomer (obtained from Preparation Example 9).
[0086] The following performance tests were performed on the low-dielectric laminates prepared in the various embodiments and comparative examples: the dielectric constant (Dk) and dielectric loss (Df) were tested using the splice post dielectric resonator (SPDR) method at a frequency of 10 GHz according to IPC-TM-650 2.5.5.9. The glass transition temperature (Tg) was tested using differential scanning calorimetry (DSC), and the coefficient of thermal expansion (CTE) was determined according to IPC-TM-650 2.4.41 in thermomechanical analysis mode. Copper foil peel strength was tested according to IPC-TM-650 2.4.8 standard, while heat resistance was evaluated by 288℃ immersion tin test (floating solder test). According to IPC-TM-650 2.4.13 standard, the laminate sample was immersed in a tin bath at 288℃ for a specified time, and the presence of blistering or delamination on the sample surface was observed and recorded to comprehensively determine its heat resistance reliability.
[0087] Table 1 shows the test results of the laminates in each embodiment and comparative example.
[0088] Table 1
[0089] As shown in Table 1, Examples 1-4 of this application all passed the tin immersion test at 288°C and exhibited extremely low dielectric loss and excellent heat resistance. Among them, Example 2 had the best overall performance, with a dielectric loss as low as 0.00042@10GHz, a glass transition temperature of 285°C, and a peel strength of 0.72N / mm, combining excellent electrical properties, heat resistance, and mechanical toughness. Example 4, with its high crosslinking density and high filler content, achieved a glass transition temperature as high as 305°C and an ultra-low coefficient of thermal expansion of 7ppm / °C.
[0090] In Comparative Example 1, due to the excessive use of 3,3'-dichloromethylbiphenyl, the excess bifunctional electrophilic reagent triggered severe side reactions, leading to a significant decrease in the purity of the target product. The dielectric loss of its laminate increased to 0.00180, the glass transition temperature dropped to 205℃, and delamination and bubbling occurred during the tin immersion test at 288℃. In Comparative Example 2, due to the excessive use of 4-vinylbenzyl chloride, the excess 4-vinylbenzyl chloride underwent a by-polymerization reaction under the action of highly reactive vinyl groups, generating a large amount of oligomeric impurities. The dielectric loss of its laminate reached 0.00150, the glass transition temperature was only 215℃, and delamination and bubbling also occurred during the tin immersion test. Comparative Example 3 replaced the strong base sodium hydroxide with the weak base sodium carbonate, resulting in the inability to effectively remove the proton from the indene ring methylene group in the reaction system. The nucleophilic substitution reaction was essentially impossible, leading to extremely low yields of indene-containing monomers. The dielectric loss of its laminate was 0.01200 N / mm, the glass transition temperature was only 155°C, and the peel strength was as low as 0.15 N / mm. The tin-immersion test showed severe delamination and intense blistering. Comparative Example 4, by replacing the indene-containing monomers with an equal amount of benzocyclobutene monosubstituted divinylbenzene monomers, passed the tin-immersion test, but its dielectric loss and glass transition temperature were worse than those of the embodiments in this application. This demonstrates that the indene-containing structure of this application has significant technical advantages in reducing dielectric loss and improving heat resistance.
[0091] Therefore, those skilled in the art should recognize that although numerous exemplary embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Thus, the scope of the present invention should be understood and construed as covering all such other variations or modifications.
Claims
1. A low-dielectric material, characterized in that, The low dielectric material comprises the following raw materials in parts by weight: 5-80 parts of indene-containing monomers and / or indene-containing resins, 5-40 parts of unsaturated polydiolefin resins, 5-40 parts of saturated hydrocarbon resins, 30-120 parts of fillers, 0.3-10 parts of thermal initiators, 10-50 parts of flame retardants, and 0-30 parts of crosslinking agents.
2. The low-dielectric material according to claim 1, characterized in that, The low-dielectric material also includes 30-65 parts by weight of reinforcing material.
3. The low-dielectric material according to claim 1, characterized in that, In the unsaturated polydiolefin resin, the molar content of unsaturated carbon-carbon double bonds is 2%-20%.
4. The low-dielectric material according to claim 1, characterized in that, The unsaturated polydiolefin resin has a viscosity of 0.1-100 Pa·s at 25°C, or the unsaturated polydiolefin resin is solid at 25°C.
5. The low-dielectric material according to claim 1, characterized in that, The number average molecular weight of the unsaturated polydiolefin resin is 1000-10000.
6. The low-dielectric material according to claim 1, characterized in that, The saturated hydrocarbon resin has a number average molecular weight of 1,000-100,000, and includes one or more of the following: saturated polybutadiene resin, hydrogenated styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer.
7. The low-dielectric material according to claim 1, characterized in that, The structural formula of the indene-containing monomer is: (1), R1 is independently selected from any one of hydrogen atom, methyl, methoxy, ethyl, and ester group; R2 is selected from any one of hydrogen atom, methyl, methoxy, ethyl, or ester group; R3 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, or aliphatic chains containing 1-10 carbon atoms; R4 is selected from any one of hydrogen atom, methoxy group, ester group, or aliphatic chain containing 1-10 carbon atoms; R5 is selected from any one of hydrogen atoms, methoxy groups, or aliphatic chains containing 1 to 10 carbon atoms; R6 is selected from any one of the following: phenyl, naphthyl, biphenyl, aromatic alkyl, aliphatic chain containing 1-10 carbon atoms, or a substituent containing halogen atoms.
8. The low-dielectric material according to claim 7, characterized in that, The structural formula of the indene-containing resin is: (2) or (3), In structural formulas (2) and (3), CO represents the polymerization of monomer (1) and monomer M2: R1 is independently selected from any one of hydrogen atom, methyl, methoxy, ethyl, and ester group; R2 is selected from any one of hydrogen atom, methyl, methoxy, ethyl, or ester group; R3 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, or aliphatic chains containing 1-10 carbon atoms; R4 is selected from any one of hydrogen atom, methoxy group, ester group, or aliphatic chain containing 1-10 carbon atoms; R5 is selected from any one of hydrogen atoms, methoxy groups, or aliphatic chains containing 1 to 10 carbon atoms; R6 is selected from any one of phenyl, naphthyl, biphenyl, aromatic alkyl, aliphatic chain containing 1-10 carbon atoms, or a substituent containing halogen atoms; n is selected from integers ≥1 and ≤1000; m is selected from integers ≥ 0 and ≤ 1000; m' is selected from integers ≥0 and ≤1000; And m+n+m'≥2; When the indene-containing resin is polymerized, R7 is an independent terminal or hydrogen atom of the initiator; When the indene-containing resin is not polymerized, R7 is independent of each other. Or hydrogen atoms.
9. A semi-cured sheet, characterized in that, The prepreg is made from the low dielectric material as described in any one of claims 2-8.
10. The application of the prepreg according to claim 9 in a semiconductor device.